Risk Factors of Colorectal Cancer Other than Genetic Factors at Jinnah Post Graduate Medical Center - Hayat, Muhammad Hayat; Ghulam Haider; Raja Rahool; Saima Zahoor; Shakeel Akbar; Perwasha Kerio (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the association of different risk factors other than genetic factors in patients having colorectal carcinoma.Study Design: Case control study.Place and Duration of Study: Medical Oncology Department, Jinnah Postgraduate Medical Center, Karachi Pakistan, from Jan 2019 to Jan 2020.Methodology: A total of 200 patients of age more than 10 years of either gender were included in the study. Hundred were cases of newly diagnosed colorectal cancer and 100 were healthy controls. The data regarding socio-demographics and risk factors other than genetic risk factors was collected through pre-designed questionnaire.Results: The mean age of the cases was 42.76±15.02 & the controls were 39.42±14.03 years. After adjusting odds in multivariate analysis, physically inactive (OR=0.40; 95% CI: 0.16-0.98, p